Cognitive Interviewing during Pretesting of the Prefinal Afrikaans for the Western Cape Disabilities of the Arm, Shoulder and Hand Questionnaire following Translation and Cross-Cultural Adaptation - Susan de Klerk; Christina Jerosch-Herold; Helen Buchanan; Lana van Niekerk (Occupational Therapy International)
When patient-reported measures are translated and cross-culturally adapted into any language, the process should conclude with cognitive interviewing during pretesting. This article reports on translation and cross-cultural adaptation of the Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire into Afrikaans (for the Western Cape). This qualitative component of a clinical measurement, longitudinal study was aimed at the pretesting and cognitive interviewing of the prefinal Afrikaans (for the Western Cape) DASH questionnaire highlighting the iterative nature thereof. Twenty-two females and eight males with upper limb conditions were recruited to participate at public health care facilities in the Western Cape of South Africa. Cognitive interviews were conducted as a reparative approach with an iterative process through retrospective verbal probing during a debriefing session with 30 participants once they answered all 30 items of the translated DASH questionnaire. The sample included Afrikaans-speaking persons from low socioeconomic backgrounds, with low levels of education and employment (24 of 30 were unemployed). Pragmatic factors and measurement issues were addressed during the interviews. This study provides confirmation that both pragmatic factors and measurement issues need consideration in an iterative process as part of a reparative methodology towards improving patient-reported measures and ensuring strong content validity.